Allostatic load in thyroid cancer is higher than that of other cancers: A secondary analysis using NHANES - Wen-rui Wang; Guan-dong Liu; Dong-xiao Ren; Xiao-Yu Liu (PLoS ONE, 2026)
Background To compare the levels of allostatic load score (ALS) between thyroid cancer patients and patients with other types of cancer and explore whether ALS mediates the association between thyroid cancer and alterations in physiological function. Methods This cross-sectional study conducted a secondary analysis of 181 cancer patients using NHANES data from 2007 to 2020, including 91 individuals with thyroid cancer. Generalized linear regression, logistic regression, and sensitivity analysis were used to analyze the association between thyroid cancer and ALS in three different models. Receiver operating characteristic (ROC) curve analysis and feature importance analysis were utilized to assess the clinical predictive value of thyroid cancer. We also conducted a series of mediation analyses to examine the mediating role of ALS. Results The ALS in thyroid cancer patients was higher than that in other cancer types ( P < 0.05). Thyroid cancer was significantly associated with ALS even after adjusting for demographic variables (β = 0.770, 95%CI: 0.315–1.480; OR=2.255, 95%CI: 1.111–4.575). This association remained robust to missing data (all P < 0.05) and was not confounded by drinking, diabetes, or thyroid disease (all P > 0.05). Although thyroid cancer had limited predictive value on ALS, it exerted strong explanatory power. The mediation analysis conducted with imputed data and adjusted for confounding variables revealed that ALS fully mediated the effect of thyroid cancer on red cell distribution width (RDW) (IE: β = 0.103, P = 0.008; DE: β = 0.389, P = 0.056), with a mediation proportion of 20.93%. Conclusion Our findings revealed that thyroid cancer condition were associated with elevated AL. AL mediated the relationship between thyroid cancer and RDW.